CD8+ T cells control SIV infection using both cytolytic effects and non-cytolytic suppression of virus production - Benjamin B. Policicchio; Erwing Fabian Cardozo-Ojeda; Cuiling Xu; Dongzhu Ma; Tianyu He; Kevin D. Raehtz; Ranjit Sivanandham; Adam J. Kleinman; Alan S. Perelson; Cristian Apetrei; Ivona Pandrea; Ruy M. Ribeiro (Nature Communications, 2023)
Abstract Whether CD8+ T lymphocytes control human immunodeficiency virus infection by cytopathic or non-cytopathic mechanisms is not fully understood. Multiple studies highlighted non-cytopathic effects, but one hypothesis is that cytopathic effects of CD8+ T cells occur before viral production. Here, to examine the role of CD8+ T cells prior to virus production, we treated SIVmac251-infected macaques with an integrase inhibitor combined with a CD8-depleting antibody, or with either reagent alone. We analyzed the ensuing viral dynamics using a mathematical model that included infected cells pre- and post- viral DNA integration to compare different immune effector mechanisms. Macaques receiving the integrase inhibitor alone experienced greater viral load decays, reaching lower nadirs on treatment, than those treated also with the CD8-depleting antibody. Models including CD8+ cell-mediated reduction of viral production (non-cytolytic) were found to best explain the viral profiles across all macaques, in addition an effect in killing infected cells pre-integration (cytolytic) was supported in some of the best models. Our results suggest that CD8+ T cells have both a cytolytic effect on infected cells before viral integration, and a direct, non-cytolytic effect by suppressing viral production.